2010
DOI: 10.1093/schbul/sbq151
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Kynurenic Acid During Adolescence Produces Memory Deficits in Adulthood

Abstract: The glia-derived molecule kynurenic acid (KYNA) is an antagonist of a7 nicotinic acetylcholine receptors and the glycine B binding site on n-methyl-d-aspartateglutamate receptors, both of which have critical roles in neural plasticity as well as learning and memory. KYNA levels are increased in the brains and cerebral spinal fluid of persons with schizophrenia, leading to the notion that changes in KYNA concentration might contribute to cognitive dysfunction associated with this disorder. Indeed, recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 61 publications
6
50
0
Order By: Relevance
“…This dose of kynurenine results in a 2-3 fold increase in KYNA concentration in juvenile and adult rats (Akagbosu et al, 2012; Erhardt et al, 2004), mirroring the magnitude of the increase observed in schizophrenia (Erhardt et al, 2001; Schwarcz et al, 2001). Using kynurenine to manipulate KYNA concentration also has high translational value since an increase in kynurenine level is a primary factor leading to the increased KYNA concentration associated with schizophrenia (Miller et al, 2006; Linderholm et al, 2012).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…This dose of kynurenine results in a 2-3 fold increase in KYNA concentration in juvenile and adult rats (Akagbosu et al, 2012; Erhardt et al, 2004), mirroring the magnitude of the increase observed in schizophrenia (Erhardt et al, 2001; Schwarcz et al, 2001). Using kynurenine to manipulate KYNA concentration also has high translational value since an increase in kynurenine level is a primary factor leading to the increased KYNA concentration associated with schizophrenia (Miller et al, 2006; Linderholm et al, 2012).…”
Section: Introductionmentioning
confidence: 72%
“…Consistent with this hypothesis, recent studies have shown that treating rats with kynurenine throughout adolescence (PND 27-53) increases KYNA levels during the treatment period, and produces memory deficits and decreased social behavior when rats are tested as adults, despite having normal KYNA levels at the time of behavioral testing (Akagbosu et al, 2012; Trecartin & Bucci, 2011). Similarly, treating rat dams with kynurenine-enriched food from gestational day 15 to PND 21 increased KYNA concentration in the offspring, which later exhibited impaired attention and memory as adults (Alexander et al, 2013; Pocivavsek et al, 2012).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Sequential systemic injections of kynurenine from PND 7 to 16 in mice (Liu et al, 2014) or PND 7 to 10 in rats (Iaccarino et al, 2013) result in enhanced amphetamine-induced locomotor activity and deficits in social interaction, respectively. Intermittent treatment of adolescent rats with systemic injections of kynurenine results in impaired hippocampal-mediated cognition, assessed by novel object recognition and contextual fear memory, as well as dysfunctional social interaction in adulthood (PND 61) (Akagbosu et al, 2012; Trecartin and Bucci, 2011). Importantly, this intermittent adolescent kynurenine treatment paradigm results in dysfunctional LTP after a burst of high-frequency stimulation (DeAngeli et al, 2014).…”
Section: Pre- and Postnatal Kp Manipulation To Study Neuropathologmentioning
confidence: 99%
“…The detrimental consequences of elevated KYNA levels on glutamatergic neurotransmission and cognitive and behavioral processes have been widely demonstrated in animals with elevated brain KYNA levels, produced by administration of the precursor, L-kynurenine (KYN; Akagbosu et al, 2010; Alexander et al, 2013; Chess et al, 2007, 2009; Trecartin and Bucci, 2011; Konradsson-Geuken et al, 2010). These findings have suggested that drugs that reduce brain KYNA levels may benefit cognitive function in a wide range of patient groups (e.g., Wonodi and Schwarcz, 2010).…”
Section: Introductionmentioning
confidence: 99%